2023
DOI: 10.1177/10778012231192585
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Polyvictimization and Health Outcomes

Abstract: This study examines how gender interacts with polyvictimization patterns in survivors’ health problems using 8,587 survivors of intimate partner violence from the National Intimate Partner and Sexual Violence Survey, a nationally representative sample collected in 2010. Polyvictimization included six categories that were created in our previous work: sexual violence, physical and psychological violence, coercive control, multiple violence, stalking, and psychological aggression. Multiple violence was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Polyvictimisation, with multiple forms of violence experienced, and multiple distinct acts of violence were the strongest predictors of symptoms of depression and anxiety in our study. This is supported by other recent studies which have shown that experiencing multiple forms of IPV can increase survivors' vulnerability to health sequelae such as headaches, chronic pain and sleep difficulties (94), as well as poor mental health (95,96). Cantu and colleagues found that when looking at cyber IPV, there was an additive effect of multiple types of cyber abuse on symptoms of depression, with people who experienced all three types of cyber abuse having a 2.15 unit increase in depression score after controlling for face-to-face IPV (20).…”
Section: Discussionsupporting
confidence: 63%
“…Polyvictimisation, with multiple forms of violence experienced, and multiple distinct acts of violence were the strongest predictors of symptoms of depression and anxiety in our study. This is supported by other recent studies which have shown that experiencing multiple forms of IPV can increase survivors' vulnerability to health sequelae such as headaches, chronic pain and sleep difficulties (94), as well as poor mental health (95,96). Cantu and colleagues found that when looking at cyber IPV, there was an additive effect of multiple types of cyber abuse on symptoms of depression, with people who experienced all three types of cyber abuse having a 2.15 unit increase in depression score after controlling for face-to-face IPV (20).…”
Section: Discussionsupporting
confidence: 63%
“…IPV survivors often experience negative physical, and emotional impacts, such as acute illnesses like respiratory and urinary tract problems, and chronic disorders like migraines and gastrointestinal diseases [ 8 ]. It has been found that women who have experienced IPV are more likely to have poor health such as overweight, substance abuse and eating disorders [ 9 ]. In addition to physical health, IPV survivors often report negative mental health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed a correlation between the intensity of IPV experienced and a subsequent deterioration in mental health status. Cho et al, [ 9 ] analyzed the relationship between physical health outcomes and IPV using the NISVS, with no in-depth exploration of mental health conditions. Similarly, Alroy et al, [ 19 ] used New York City Community Health Survey data to analyze the prevalence of IPV, health status and behaviors, which found that adults who had experienced psychosocial IPV had a higher prevalence of not getting the treatment they needed for their mental health problems and perceived poorer health status.…”
Section: Introductionmentioning
confidence: 99%